Beauty in the shadow of neurodegenerative disease: a narrative review on aesthetic experience, neural mechanisms, and therapeutic frontiers - Calderone, Andrea; De Luca, Rosaria; Calapai, Rosalia; Mirabile, Alessio; Quartarone, Angelo; Calabrò, Rocco Salvatore (Frontiers in Human Neuroscience, 2025)
Neuroaesthetics, an emerging field at the intersection of neuroscience, psychology, and the arts, offers new perspectives on the biological and cognitive mechanisms of aesthetic experience. This narrative review explores the convergence of neuroaesthetics and neurodegenerative disorders, focusing on Alzheimer’s disease, Parkinson’s disease, frontotemporal dementia, and Huntington’s disease. Drawing on evidence from neuroimaging, neuropsychology, and clinical studies, we examine how neurodegenerative processes differentially disrupt the neural systems of the “aesthetic triad”: sensory-motor, emotion-valuation, and meaning-knowledge. Such disruptions not only impair patients’ ability to perceive and create art but may also reveal unexpected creative capacities. We discuss the therapeutic potential of arts-based interventions, highlighting the benefits of personalized and technology-driven approaches, including immersive virtual reality and digital art platforms, to enhance neurorehabilitation and psychological wellbeing. The “Michelangelo effect,” where engagement in meaningful aesthetic activities supports learning, motivation, and resilience, exemplifies this translational potential. Our synthesis underscores clinical, neuroscientific, and rehabilitative implications, while noting ongoing challenges such as the need for standardized outcomes and interdisciplinary collaboration. Integrating neuroaesthetic principles into neurorehabilitation may help preserve cognitive and motor functions and enrich quality of life and self-concept in people with neurodegenerative disease. Future research should optimize these approaches to ensure meaningful benefits for patients.